PELAKSANAAN FUNGSI PENGAWASAN YANG DILAKUKAN OLEH BAPAS TERHADAP PELAKU TINDAK PIDANA ANAK YANG TELAH MENERIMA KESEPAKATAN DIVERSI DI WILAYAH HUKUM KEPOLISIAN INDRAGIRI HULU - Mardiansyah, Khairil; Deliana, Evi; R, Mukhlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Regarding the examination of the reported, the investigator asks the reported party to be accompanied by the Bapas and Legal Counsel. During the examination process at the lidik level, Bapas was not present to supervise and assist children. From the information of the police investigator, Inhu said that Bapas was not present to supervise and assist children in the examination process at the level of investigations in taking children's information.This research uses a sociological juridical approach. Sociological juridical research or empirical research is an approach by looking at the facts that occur in the field. While the nature of the research is descriptive which aims to provide a clear picture of the problem under study.The implementation of the supervisory function carried out by the Bapas against the perpetrators of child crimes, the implementation rules of diversion, the implementing rules in a legal policy are very important. With regulations, law enforcement officers have guidelines for taking action. In the case of children, diversion is a very important policy applied to protect children from the formal justice process. However, sometimes the authorities still hesitate to do it. This is due to community demands, politics, or other matters that are taken into account by the authorities. The authorities are also afraid of being blamed in the future if the perpetrator repeats his actions. The public is also still pessimistic that the apparatus diversion policy will harm the interests of certain parties. Constraints in the implementation of the supervisory function carried out by Bapas, Internal Obstacles, namely different understanding, lack of cooperation between the parties involved, ethical problems and bureaucratic obstacles, coordination between law enforcement officials and there is no common perception among law enforcement officers.Keywords: Supervision - Correctional Center – Children